Tujjar in the Gulf: Changes in Political Influence - Lakshmi Venugopal Menon (15445334) (2023)
Since the oil boom in the 1970s, the Gulf region has witnessed tremendous growth. Today, the GCC countries have an impressive collective 85% urbanization. This paper argues that merchant-ruler relations and the transnational dynamism of the Gulf played crucial roles in the traditional development and evolution of urban cities in the GCC. It argues that pivoting to a Western-European city concept devoid of an appreciation of the GCC’s transnational dimension and the region’s perennial structural need for migrant labor is imprudent. This chapter aims to fill the existing gap in the literature and urges the GCC countries to increase local participation to offset an observed Orientalist approach to Gulf urbanism. Thus, making the case for the creation of sustainable city concepts that appreciate the transnational nature of the Gulf region. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_5